PERANAN VISUM ET REPERTUM SEBAGAI ALAT BUKTI PADA PROSES PENYIDIKAN TINDAK PIDANA PEMBUNUHAN DI POLRESTA DENPASAR - Putu Jaya Kusuma; Ni Luh Gede Yogi Arthani (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
Referring to Article 133 of the Criminal Procedure Code, for the crime of murder the investigator may request the assistance of an expert doctor to assist the investigation process. Assistance for examination of expert doctors is stated in writing in the Visum et Repertum, which is useful as evidence needed by investigators in the investigation file. The problems studied in this research are: 1) The role of Visum et Repertum in the process of investigating the crime of murder at the Denpasar Police. 2) Obstacles for investigators and forensic doctors in the investigation through evidence of Visum et Repertum at the Denpasar Police. The research method used is the empirical legal research method. The result of this study is that Visum et Repertum has played a role as documentary evidence to complete the investigation file for the crime of murder at the Denpasar Police. The obstacles encountered are related to time in terms of conducting an examination or autopsy of the corpse with the relationship between time to conduct an investigation by investigators, because the doctor needs to be careful in carrying out body examinations.